2014
DOI: 10.4012/dmj.2013-243
|View full text |Cite
|
Sign up to set email alerts
|

Dental zirconia can be etched by hydrofluoric acid

Abstract: The surface morphology and crystal structure change of dental zirconia after hydrofluoric acid (HF) etching were evaluated. Four groups of sintered zirconia specimens were 1) control group, 2) immersion in 9.5%HF at 25 o C for 1, 2, 3, or 24 h, 3) immersion in 9.5%HF at 80o C for 1, 3, 5, or 30 min and 4) immersion in 48%HF at 25 o C for 30 or 60 min. The specimens were evaluated under SEM and XRD. The SEM analysis revealed changes in surface topography for all the HF-etched zirconia specimens. The irregularit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
78
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 58 publications
7
78
1
5
Order By: Relevance
“…Therefore, it may not be appropriate to overemphasize the effects of surface roughening according to the decrease in marginal effectiveness. On the other hand, different from the results of a previous study (Sriamporn et al, 2014) in which it was claimed that etching zirconia elicited the transformation in the crystalline structure from tetragonal to monolithic phase, no phase transformation could be detected in both two etching groups in the current study. Nevertheless, the rapid dissolution of surface layer in zirconia as well as the formation of deep porous structures might still cause the decrease in the mechanical strength.…”
Section: Discussioncontrasting
confidence: 85%
“…Therefore, it may not be appropriate to overemphasize the effects of surface roughening according to the decrease in marginal effectiveness. On the other hand, different from the results of a previous study (Sriamporn et al, 2014) in which it was claimed that etching zirconia elicited the transformation in the crystalline structure from tetragonal to monolithic phase, no phase transformation could be detected in both two etching groups in the current study. Nevertheless, the rapid dissolution of surface layer in zirconia as well as the formation of deep porous structures might still cause the decrease in the mechanical strength.…”
Section: Discussioncontrasting
confidence: 85%
“…Surface treatment methods and selection of resin cements are key methods that could increase retention of the restorations with the tooth. Although chemical surface conditioning using hydrofluoric acid has been known to be inadequate for zirconia, recent studies have reported that in different concentrations and temperature, hydrofluoric acid could induce change in the zirconia surfaces 10. Cavitations were found on zirconia surfaces in SEM images taken after surface conditioning using 9.5% hydrofluoric acid at room temperature for 1, 2, 3, and 24 hours, in 80℃ for 1, 3, 5, and 30 minutes, and using 48% hydrofluoric acid for 30 and 60 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…This report indicated well-established clinical evidence that sandblasting at a moderate pressure and using primers containing phosphate monomer and/or luting resins provide long-term durable bonding to zirconia. In addition, alternative approaches i.e., laser, acid, and low-fusing glaze porcelain coating treatments have been introduced [15,16,17]. However, the clinical evidence of these alternative methods is yet unclear.…”
Section: Introductionmentioning
confidence: 99%